I'll Marry You If You Get Me a Job: Cross-Nativity Marriages and Immigrant Employment Rates - Delia Furtado; Nikolaos Theodoropoulos (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2008)
This paper tests whether marriage to a native affects the probability that an immigrant is employed. We provide a theoretical background which explains how marriage to a native may positively or negatively affect an immigrant's employment probability. Utilizing the 2000 U.S. Census, we first look at the effect of cross-nativity marriages on employment using a linear probability model. Then, we estimate a two stage least squares model instrumenting for cross-nativity marriages using local marriage market conditions. Results from a linear probability model controlling for the usual measures of human capital and immigrant assimilation suggest that marriage to a native increases the employment probability of an immigrant by approximately 5 percentage points. When controlling for the endogeneity of the intermarriage decision, marriage to a native increases the employment probability by about 11 percentage points. We provide alternative explanations and suggest policy implications.
Keywords: J12; I21; J61; 330; Intermarriage; Employment; Immigration